Revealing cryptic interactions between large mammalian herbivores and plant‐dwelling arthropods via DNA metabarcoding - Tali S. Berman; Moshe Inbar (Ecology, 2022)
In the past decade, it has become clear that omnivory, feeding on more than one trophic level, is important in natural and agricultural systems. Large mammalian herbivores (LMH) frequently encounter plant‐dwelling arthropods (PDA) on their food plants. Yet, ingestion of PDA by LMH is only rarely addressed and the extent of this direct trophic interaction, especially at the PDA community level, remains unknown. Using a DNA‐metabarcoding analysis on feces of free‐ranging cattle from a replicated field experiment of heavily and moderately grazed paddocks, we reveal that feeding cattle (incidentally) ingest an entire food chain of PDA including herbivores, predators and parasites. Overall, 25 families of insects and four families of arachnids were ingested, a pattern that varied over the season, but not with grazing intensity. We identified the functional groups of PDA vulnerable to ingestion, such as sessile species and immature life stages. Most of the fecal samples (76%) contained sequences belonging to PDA, indicating that direct interactions are frequent. This study highlights the complex trophic connections between LMH and PDA. It may even be appropriate to consider LMH as omnivorous enemies of PDA.

Direct consumptive interactions between mammalian herbivores and plant-dwelling invertebrates: prevalence, significance, and prospectus - Moshe Gish; Matan Ben-Ari; Moshe Inbar (Oecologia, 2017)

Differences in Monoterpene Biosynthesis and Accumulation in Pistacia palaestina Leaves and Aphid-Induced Galls - Karin Rand; Einat Bar; Matan Ben Ari; Rachel Davidovich-Rikanati; Natalia Dudareva; Moshe Inbar; Efraim Lewinsohn (Journal of Chemical Ecology, 2017)

The Mono - and Sesquiterpene Content of Aphid-Induced Galls on Pistacia palaestina is Not a Simple Reflection of Their Composition in Intact Leaves - Karin Rand; Einat Bar; Matan Ben-Ari; Efraim Lewinsohn; Moshe Inbar (Journal of Chemical Ecology, 2014)

Pollen on-twine for food provisioning and oviposition of predatory mites in protected crops - Einat Adar; Moshe Inbar; Shira Gal; Samuel Gan-Mor; Eric Palevsky (BioControl, 2014)

The role of onion-associated fungi in bulb mite infestation and damage to onion seedlings - Tal Ofek; Shira Gal; Moshe Inbar; Sara Lebiush-Mordechai; Leah Tsror; Eric Palevsky (Experimental and Applied Acarology, 2014)

Do individuals with a family history of colorectal cancer adhere to medical recommendations for the prevention of colorectal cancer? - Karen Bronner; Ilse Mesters; Ahuva Weiss-Meilnik; Ravit Geva; Guy Rozner; Hana Strul; Moshe Inbar; Zamir Halpern; Revital Kariv (Familial Cancer, 2013)

Red gall pigmentation: cytokinin stimulation is not everything - Yoram Gerchman; Simcha Lev-Yadun; Moshe Inbar (Arthropod-Plant Interactions, 2013)

Plant-feeding and non-plant feeding phytoseiids: differences in behavior and cheliceral morphology - Einat Adar; Moshe Inbar; Shira Gal; Noam Doron; Zhi-Qiang Zhang; Eric Palevsky (Experimental and Applied Acarology, 2012)

Genetic structure of a galling aphid Slavum wertheimae and its host tree Pistacia atlantica across an Irano-Turanian distribution: from fragmentation to speciation? - Sarit Avrani; Rachel Ben-Shlomo; Moshe Inbar (Tree Genetics & Genomes, 2012)

Avoiding incidental predation by mammalian herbivores: accurate detection and efficient response in aphids - Moshe Gish; Amots Dafni; Moshe Inbar (The Science of Nature, 2011)

Modification of tree architecture by a gall-forming aphid - L. Kurzfeld-Zexer; D. Wool; Moshe Inbar (Trees, 2010)

Feeding activity and dietary composition of roe deer at the southern edge of their range - Arian D. Wallach; Uri Shanas; Moshe Inbar (European Journal of Wildlife Research, 2010)

Phenotypic plasticity and gene diversity in Pistacia lentiscus L. along environmental gradients in Israel - Sagi Nahum; Moshe Inbar; Gidi Ne’eman; Rachel Ben-Shlomo (Tree Genetics & Genomes, 2008)

Host Location by Apterous Aphids After Escape Dropping from the Plant - Moshe Gish; Moshe Inbar (Journal of Insect Behavior, 2006)

The Effects of Nectar–Nicotine on Colony Fitness of Caged Honeybees - Natarajan Singaravelan; Moshe Inbar; Gidi Ne'eman; Melanie Distl; Michael Wink; Ido Izhaki (Journal of Chemical Ecology, 2006)

Feeding Responses of Free-flying Honeybees to Secondary Compounds Mimicking Floral Nectars - Natarajan Singaravelan; Gidi Nee'man; Moshe Inbar; Ido Izhaki (Journal of Chemical Ecology, 2005)

Conspicuous and aposematic spines in the animal kingdom - Moshe Inbar; Simcha Lev-Yadun (The Science of Nature, 2005)

The Role of Plant Rapidly Induced Responses in Asymmetric Interspecific Interactions Among Insect Herbivores - Moshe Inbar; Hamed Doostdar; Gary L. Leibee; Richard T. Mayer (Journal of Chemical Ecology, 1999)

Elicitors of Plant Defensive Systems Reduce Insect Densities and Disease Incidence - Moshe Inbar; Hamed Doostdar; Ronald M. Sonoda; Gary L. Leibee; Richard T. Mayer (Journal of Chemical Ecology, 1998)